1980
DOI: 10.1128/jvi.33.1.52-58.1980
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of vesicular stomatitis virus particles: implications for virion assembly

Abstract: Vesicular stomatitis virus (VSV) particles formed at early times after infection contain only one-third the amount of viral glycoprotein (G protein), relative to the major internal structural proteins M and N, as is found in particles released later. These "early" particles also have a lower density in equilibrium sucrose gradients than do those formed later; however, the sedimentation velocity and specific infectivity of these two classes of particles are the same. VSV-infected cells also release virus-like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…This is consistent with the facts that (i) M binds to the plasma membrane of infected cells (30), (ii) M selfaggregates under certain conditions (4), and (iii) M is a late function, presumably involved in the assembly of virions (2). Alternatively, it has been suggested that viral nucleocapsids may be involved in clustering of G, perhaps in association with M (26).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with the facts that (i) M binds to the plasma membrane of infected cells (30), (ii) M selfaggregates under certain conditions (4), and (iii) M is a late function, presumably involved in the assembly of virions (2). Alternatively, it has been suggested that viral nucleocapsids may be involved in clustering of G, perhaps in association with M (26).…”
Section: Discussionsupporting
confidence: 87%
“…The molecular interactions occurring during assembly of VSV are ill defined. It is clear from a number of previous studies that clustering of G occurs in the plasma membrane of infected cells; most host glycoproteins are excluded from released virions (26), and clusters of G-can be seen in areas of the cell membrane active in virus assembly (39). The functions (viral or host) required for this clustering are not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear from numerous studies that M protein is essential for assembly of VSV virions (26,27,49). Maturation of the condensed RNP-M complex at the infected cell membrane can take place in the absence of G protein, suggesting that interaction of M protein with the cell membrane is sufficient to promote envelopment and budding of the VSV virion.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleocapsids appear to be necessary for the production of authentic bacilliform particles; the formation of abnormal particles which lack a nucleocapsid is very rare in wild-type virus infections but does occur with certain temperature-sensitive viral mutants (43). The viral envelope contains a variable amount of the transmembrane protein G (29). In differentiated epithelial cells, G protein is transported predominantly to the basolateral plasma membrane, and VSV buds almost exclusively from this membrane domain (38,39).…”
mentioning
confidence: 99%